Entre janelas e camarotes : o sagrado e o profano na festa do Bom Jesus dos Navegantes de Penedo/AL - Guimarães, Esmeraldo Victor Cavalcante (2014)
The research reflects on the Feast of Bom Jesus dos Navegantes there is 130 years in the city of Alagoas Penedo with the realization of one of the most significant fluvial processions of the São Francisco River. The overall objective was to examine the relationship of the sacred and the profane and understand the festive arrangement production processes, while emptying the real meaning of the feast, fills people, the place and outside it, in moments of celebration. Analysis guided the qualitative approach favored source documents, interviews and observations about the history and the party floor with empirical work in the festivities of the years 2013 and 2014. The memory of respondents - loyal, party-goers and organizers - was useful for the assessment of changes in the Feast of the Bom Jesus dos Navegantes. We identified these 130 years of festivities two arrangements that are distinguished by the insertion of activities and the duration of the party, namely the sacred and the profane Arrano arrangement. It was found that the party historically functions as complex socio-cultural entity, producer and bearer of an identity that you will be given the intentions and practices of those who organize it. It is evident that those who weave the party building, year by year, always promote a singular form. The Penedense people over the 130 years the party has taken turns in the task of building the parties and keep the tradition. Each party bears the mark of time and technique that is available to society at every time.